Long working hours and physical activity. Issue 8 (12th March 2015) - Angrave, David; Charlwood, Andy; Wooden, Mark
Abstract : Background: It is widely believed that persons employed in jobs demanding long working hours are at greater risk of physical inactivity than other workers, primarily because they have less leisure time available to undertake physical activity. The aim of this study was to test this hypothesis using prospective data obtained from a nationally representative sample of employed persons. Methods: Longitudinal data from the Household, Income and Labour Dynamics in Australia Survey (93 367 observations from 17 893 individuals) were used to estimate conditional fixed effects logistic regression models of the likelihood of moderate or vigorous physical exercise for at least 30 min, at least four times a week. Results: No significant associations between long working hours and the incidence of healthy levels of physical activity were uncovered once other exogenous influences on activity levels were controlled for. The odds of men or women who usually work 60 or more hours per week exercising at healthy levels were 6% and 11% less, respectively, than those of comparable persons working a more standard 35–40 h/week; however, neither estimate was significantly different from 0 at 95% CI. Conclusions: The findings suggest that there is no trade-off between long working hours and physical activity in Australia. It is argued that these findings are broadly consistent with previous research studies from Anglo-Saxon countries (where long working hours are pervasive) that employed large nationally representative samples.